Impacts of grassland vegetation cover on the active‐layer thermal regime, northeast Qinghai‐Tibet Plateau, China - Genxu Wang; Lin'an Liu; Guangsheng Liu; Hongchang Hu; Taibin Li (Permafrost and Periglacial Processes)
The impact of vegetation cover on the active‐layer thermal regime was examined in an alpine meadow located in the permafrost region of Qinghai‐Tibet over a three‐year period. A high vegetation cover (93%) delayed thawing and freezing at a given depth relative to sites with lower covers (65%, 30% and 5%). Low vegetation covers exhibited greater annual variability in soil temperatures, and may be more sensitive to changes in air temperature. Low vegetation covers are also linked to higher thermal diffusivity and thermal conductivity in the soils. The maintenance of a high vegetation cover on alpine meadows reduces the impact of heat cycling on the permafrost, may minimise the impact of climate change and helps preserve the microenvironment of the soil. Copyright © 2010 John Wiley & Sons, Ltd.